Improving health and wellbeing in women's secure services: physical activity, appearance, self-care and body image. Issue 4 (9th December 2014) - H. Taylor, Valerie; Long, Clive; Mason, Fiona
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Lifestyle change to improve physical health is a significant challenge in secure psychiatric hospitals for women. In addition to factors that contribute to an obesogenic environments body image, self-care, self-esteem, and motivational problems compound efforts to increase physical activity and to lose weight. The paper aims to discuss these issues. Design/methodology/approach – Two elements of a comprehensive programme to improve physical health and mental wellbeing are discussed. The first describes the development of a unique role of self-care and body image therapists and an evaluation of the effects of treatment. The second describes initiatives to assess the environmental and therapeutic milieu contingencies that impact on physical activity and to increase engagement in exercise through motivational strategies. Findings – Research within the current settings has resulted in a validation of the role of the self-care and body image therapist. Other evaluations have described the environmental contingencies that impact on physical activity along with strategies to increase exercise participation. Originality/value – While much has to be learnt about how to translate awareness of the value of a healthy lifestyle for women into positive behaviour change the programme described represents part of a comprehensive and long term attempt to evaluate and improve the physical wellbeing of women in secure care.